Pengaruh Empathy Response, Anonymity, dan Customization terhadap Customer Trust pada Chatbot Customer Service Tokopedia - Mochamad Yudha Febrianta; Tegar Faiqul Hamman Basuki (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Artificial intelligence (AI) technology has grown rapidly in customer service, including AI chatbots. Tokopedia has adopted an AI chatbot for customer service, but there are still many users who do not trust it because it lacks reliability. This study aims to examine the effect of AI chatbot dimensions on customer trust in Tokopedia, focusing on the variables of empathy response, anonymity, customization, and interaction. This research is quantitative using descriptive and causal methods, involving 437 Tokopedia user respondents through structured questionnaires. Data analysis using the SEM-PLS model with SmartPLS. The results show that empathy response, anonymity, customization, and interaction have a positive and significant influence on customer trust. In addition, empathy response, anonymity, and customization also have a positive effect on interaction. The suggestion for Tokopedia is to improve the quality of chatbots in providing empathetic responses, such as greeting users, appreciating, and validating their problems. Innovation in the aspects of empathy response, anonymity, customization, and interaction is also important. Future research could explore additional factors that influence customer trust as well as the mediating or moderating effects of certain variables.